Molecular epidemiology and evolution of avian infectious bronchitis virus - Montassier, Helio Jose [UNESP] (2010)
Mutation and recombination processes are involved in the genetic and phenotypic variations of RNA viruses, leading to the emergence of new variant strains, and give rise to virus population diversity to be modeled by the host, particularly by the immune system, as occurred with infectious bronchitis virus (IBV) in chickens. The consequence is a continuous emergence of new IBV variants with regard to pathotypes, serotypes, and protectotypes. Nucleotide sequencing and subsequent genetic analysis of the S1 and N protein gene sequences provide a fast and accurate method to classify and predict IBV genotype, and a powerful instrument to monitor phylogenetic and epidemiological evolution of IBV variants. Despite the use of vaccination programmes, infectious bronchitis has become a serious problem in Brazil. Thus, a significant number of IBV field variants have been identified circulating in the Brazilian commercial poultries between 2000 to 2006 and more recently in Argentina. These viruses seem to be indigenous, because they demonstrated a low genetic relatedness with the majority of the reference strains from North America, Europe and Asia, but were moderately to highly related one to another. In summary, indigenous field IBV variants were evolving and circulating in the field in Brazil and Argentina, and should be considered as initial candidates for protection against current IBV infectious in chickens. However, in vitro and in vivo studies are needed to determine the pathogenicity and immunogenecity of these new isolates, before defining a new vaccine strain.